2021
DOI: 10.3390/clockssleep3020016
|View full text |Cite
|
Sign up to set email alerts
|

Microsleep versus Sleep Onset Latency during Maintenance Wakefulness Tests: Which One Is the Best Marker of Sleepiness?

Abstract: The interpretation of the Maintenance Wakefulness Test (MWT) relies on sleep onset detection. However, microsleeps (MSs), i.e., brief periods of sleep intrusion during wakefulness, may occur before sleep onset. We assessed the prevalence of MSs during the MWT and their contribution to the diagnosis of residual sleepiness in patients treated for obstructive sleep apnea (OSA) or hypersomnia. The MWT of 98 patients (89 OSA, 82.6% male) were analyzed for MS scoring. Polysomnography parameters and clinical data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In this way, pioneering works explored the genetic link to narcolepsy [34] and the role of orexin in narcolepsy [40]. Moreover, the link between sleepiness and circadian rhythms [13] and homeostatic pressure [1,66], have provided experimental evidence to the Borbélys' model of interplay between homeostatic processes and circadian rhythm that was theorized as early as 1982 [10] [30], the microstate analysis during MWT [5,16], or the study of stage transitions [17,35] represent metrics closely related to neurophysiology that can be extracted from electrophysiological signals already measured in sleep clinics, in order to investigate brain mechanisms related to sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, pioneering works explored the genetic link to narcolepsy [34] and the role of orexin in narcolepsy [40]. Moreover, the link between sleepiness and circadian rhythms [13] and homeostatic pressure [1,66], have provided experimental evidence to the Borbélys' model of interplay between homeostatic processes and circadian rhythm that was theorized as early as 1982 [10] [30], the microstate analysis during MWT [5,16], or the study of stage transitions [17,35] represent metrics closely related to neurophysiology that can be extracted from electrophysiological signals already measured in sleep clinics, in order to investigate brain mechanisms related to sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the MWT was better correlated with performance on driving simulator than the Multiple Sleep Latency Test (MSLT) (Pizza et al, 2009) and that driving simulator performance had a good correlation with real driving performance although not perfect (Philip et al, 2005). However, several questions remain unsolved, such as the prevalence, normative latencies, and meaning of microsleep episodes often recorded during the MWT and the dynamics of sleepiness over time (and thus the recommended periodicity of sleepiness assessment) (Boyle et al, 2008; Des Champs de Boishebert et al, 2021; Hertig‐Godeschalk et al, 2020; Morrone et al, 2020). Interestingly, we observed that an ESS score of ≥11 but not an AHI of ≥15 events/h was associated with lower MSL, which is in line with previous finding about association subjective sleepiness, impaired driving performance, and history of car crash (Budhiraja et al, 2017; Pizza et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The present study has some limitations. First, the social desirability bias may have influenced the assessment of subjective sleepiness (Des Champs de Boishebert et al, 2021 ) and the strong association between chronic and acute sleepiness precludes distinguishing the effect of each independently on neurocognitive and biological markers. Then, drivers' sleepiness could have been influenced by non-controlled confounding factors such as undiagnosed or unreported sleep or mood disorders (e.g., sleep-disordered breathing, depression).…”
Section: Discussionmentioning
confidence: 99%
“…Although subjective techniques, such as scales and questionnaires, are attractive due to their ease of use and low cost, they are sensitive to inter- and intra-individual variability. They also do not represent reliable diagnostic tools as it has been shown that it is particularly difficult to correctly perceive and self-report sleepiness (Van Dongen et al, 2004 ; Schreier et al, 2015 ; Dauvilliers et al, 2017 ; Peter-Derex et al, 2020 ; Des Champs de Boishebert et al, 2021 ). Conversely, objective techniques such as the Multiple Sleep Latency Test (MSLT) or Maintenance of Wakefulness Test (MWT), which can only be performed in few sleep laboratories, are time-consuming, far from real-life conditions, and do not correlate with subjective measures (Wise, 2006 ; Peter-Derex et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation